Highly selective bandstop filter using finite Q resonators - Socheatra, S. (Institute of Electrical and Electronics Engineers Inc., 2016)
This paper presents an approach to synthesize a highly selective microwave bandstop filter based on lossy reflection mode network. The 4th and 6th degree lowpass elliptic prototype networks have been synthesized using multiple cross-coupled Brune sections extraction to demonstrate the feasibility of the approach. Undergoing the bandpass transformation, the bandstop type behavior also known as predistorted reflection mode network can be achieved with the use of circulator. Two stages of 4th degree elliptic reflection mode network with relatively low Q resonators is synthesized to meet the bandstop filter for high power mobile interference specification. A comparison table of the Q factor required for bandpass lossy predistortion, Chebyshev and Maximally flat topologies are presented. Â© 2015 IEEE.